(untitled) (Italian Journal of Public Health, 2012)
As a result of large investments in basic science, the genomic discoveries have brought outstanding advances in understanding the molecular basis of human health. Hundreds of genes whose variations contribute to human diseases, or patients’ responses to drug treatments or even to vaccination have been discovered, laying the foundation for a paradigm shift in healthcare...